Melatonin-related alterations in Th1/Th2 polarisation in primary thymocyte cultures of pinealectomized rats - Kelestimur, Haluk; Sahin, Zafer; Sandal, Suleyman; Bulmus, Ozgur; Ozdemir, Gokcen; Yilmaz, Bayram (Academic Press Inc Elsevier Science, 2006)
[Abstract Not Available]
6th International Congress of Neuroendocrinology -- JUN 19-22, 2006 -- Pittsburgh, PA